Diversity-Oriented Synthesis of Aminocyclohexitols from Garner’s Aldehyde - Bandyopadhyay, Ayan; Mitra, Partha; Chattopadhyay, Shital K (Synthesis, 2013)
A short and efficient synthetic route to three stereoisomeric aminocyclohexane tetrols of the quercitol type has been developed from l-serine, which featured stereoselective allylation, stereocontrolled dihydroxylation, and ring-closing metathesis as key steps.
Keywords: allylation; carbocycles; dihydroxylation; metathesis; stereoselective synthesis